Macrophages in Collateral Arteriogenesis - Fung, Erik; Helisch, Armin (Frontiers in Physiology, 2012)
Arteriosclerotic vascular disease is the most common cause of death and a major cause of disability in the developed world. The adverse outcomes of arteriosclerotic vascular disease are related to the consequences of tissue ischemia and necrosis affecting the heart, brain, limbs and other organs. Collateral artery growth or arteriogenesis occurs naturally and can help restore perfusion to ischemic tissues. Understanding the mechanisms of collateral artery growth may provide therapeutic options for patients with ischemic vascular disease. Here we examine the evidence for a role of monocytes and macrophages in collateral arteriogenesis.